A comparative study on mechanical properties of fully dense 420 stainless steel parts produced by modified binder jet printing. (December 2022) - Shin, Chang-Seop; Do, Truong; Lee, Dohoon; So, Tae-Yeong; Ko, Se-Hyun; Chung, Haseung; Kwon, Patrick
Graphical abstract: Highlights: In order to tackle the deficiency of binder jet printing which retains only about 95% of full density, 5 kinds of samples were fabricated via modified binder jet printing process. Characterization of the samples made by modified binder jet printing was carried out for tensile test, fatigue test, and microstructure. The mechanical properties such as ultimate tensile test and endurance limit of binder jet printed stainless steel 420 specimens were similar or better than cold rolled stainless steel 420 specimen. Abstract: The mechanical properties of the parts produced by binder jet printing (BJP) are often considerably inferior to those of the parts produced by traditional manufacturing processes because BJP parts retain at best about 95% of theoretical density after full sintering. To address this deficiency of BJP, a new processing protocol was developed, which enables us to produce fully dense parts under an isothermal sintering condition. This paper compares the mechanical properties of the stainless steel 420 (SS420) parts produced by the several variations of this new protocol against commercially available cold rolled SS420 parts with and without the heat-treatment under the similar sintering condition used in the new protocol. The mechanical properties examined include elastic modulus and both static and fatigue strengths. The only minor drawback of the new protocol is the dimensional shrinkage occurring during sintering. However, this can be easily compensated by printing the part geometry about 15% larger in the linear dimension with the starting powder used in this study. The final results showed the excellent static and fatigue strengths of the SS420 specimens produced with the new BJP protocol, implicating the potential structural applications of the BJP parts.